OHP-076 The Incidence of Bacteremia Due to Catheters and the Cost of Antibiotics Before and After Implementation of the Zero Bacteremia Project. (12th March 2013) - Soler, A Morego; Bosó-Ribelles, A; Sanchez-Martinez, I; Arribas-Diaz, B; Titos-Arcos, JC; Sanchez-Catalicio, MM; Molina-Guillen, MP; Gil-Rueda, B; Sanchez-Mulero, MC; Manresa-Ramón, N
Abstract : Background: Primary bacteraemia and bacteraemia caused by catheter infections entail a high pharmaceutical cost. The 'Zero Bacteraemia Project' (BZP) for central intravenous catheter (CVC) use in invasive therapies showed a decrease in the number of bacteraemia cases and a financial effect on hospitalizations. Purpose: To study the number of primary bacteraemia and bacteraemia cases caused by catheter infections among patients hospitalised in our Intensive Care Unit (ICU) and the pharmaceutical cost after implementation of the CVC guides. We compared these data to those obtained from 2007–2008. Materials and Methods: We retrospectively studied 2353 patients who were admitted to our Intensive Care Unit. 1280 patients were studied before BZP (2007–2008) and 1073 after BZP implementation. The BZP implied: catheter insertion with maximal sterile barrier precautions in ICU, correct hand washing, hygienic precautions when using CVCs and the removal of unnecessary catheters. We compared the pharmaceutical cost in antibiotics in both periods. We also studied the five most-used antibiotics in this hospital for the treatment of catheter-related infections suffered by the sample group in this ICU. The data were obtained by the programme 'ENVIN-ICU'. Results: A total of 35 pre-BZP and 13 post-BZP catheter-related bacteraemia cases were detected. 5.14 and 2.17 bacteraemia cases for every 100 patients with CVC. A 37% reduction was observed in the incidence of bacteraemia. The pharmaceutical cost just in antibiotics for the 35 patients infected during the first period amounted to 3100.68 euros. However it dropped to 2388.93 euros during the following period. A 23% saving was observed on the antibiotics consumption. Conclusions: The data from this study show that the use of the 'Zero Bacteremia' policy in the process of inserting and monitoring CVCs is useful to reduce the number of infections. A statistically significant decrease in the number of bacteraemia cases and a monetary saving in antibiotics were found too. No conflict of interest.